Nursing, bedside care, and the organization of expert knowledge: Professional work as agencement. Issue 3 (September 2020) - Walter, Lars; Styhre, Alexander
Highlights: Reporting a study nursing work in a leukemia ward in a Swedish regional hospital. The study demonstrated: that conventional view of nursing as primarily being bedside care is only accommodating a subset of the totality of the nurses' work. In addition to face-to-face care and patient interaction, nursing work is the mobilization of a great number of actors with different domains of expertise to safeguard the health care status of the patient. Nursing work as agencement is opening up for alternative and more accurate understandings of nursing work in an increasingly technologically determined health care system. Abstract: Professional work such as nursing has traditionally been examined as being localized in the individual's body where professional know-how and skills are residing in the cognitive faculties and in embodied action. Contrary to such a view, the concept of agencement, recently used in the social study of finance, underlines that agency is in the contemporary technoscientifically determined times of necessity distributed and includes a variety of tempospatially distributed resources. Reporting a study nursing work in a leukemia ward in a Swedish regional hospital, it is demonstrated that the conventional view of nursing as primarily being bedside care is only accommodating a subset of the totality of the nurses' work. In addition to face-to-face care and patient interaction, nursing work is the mobilization of a great number of actors with different domains of expertise to safeguard the health care status of the patient. Speaking of nursing work as agencement is opening up for alternative and more accurate understandings of nursing work in an increasingly technologically determined health care system.